Generalization of Foraging Experience Biases Bees Toward Flowers With Complex Morphologies - Krishna, Shivani; Keasar, Tamar (Frontiers in Ecology and Evolution, 2021)
The importance of pollinators as selective agents for many floral traits is well established, but understanding their role in the evolution of complex floral shapes remains challenging. This is because pollinators often need much practice to efficiently handle morphologically complex flowers and extract their food rewards. What induces foragers to persistently visit and pollinate complex flowers despite their initial low profitability? We previously found that naive bumblebees, and unsuccessful feeding attempts of experienced ones, contribute to the pollination of complex flowers. Here we tested a complementary hypothesis, positing that successful foraging on flowers of one complex shape prepares pollinators to visit other species of different complex morphologies. We trained bumblebees to computer-controlled artificial flowers that were either simple, complex or both simple and complex. We then recorded their feeding choices and handling times on a second array of simple and complex flowers that had different shapes and required another handling technique. Bees trained on a single flower type (whether simple or complex) preferred flowers of the same type in the testing array. The foragers’ preferences after training on both flower types depended on the reward schedule during training: when both flower types rewarded equally, simple flowers were preferred at the test phase; when complex flowers provided higher reward during training, they became the preferred flower type during testing. These results suggest that successful foraging on complex flowers, especially when highly rewarding, can indeed induce insect pollinators to attempt additional flower species with other complex shapes